Persentase Mortalitas Ulat Grayak Terhadap Pemberian Ekstrak Daun Bunga Pukul Empat - Suryani, A.Irma; Hariani, Nova; Majid, Ahmad Fudhail; Risqa, Siti (Fakultas MIPA UNM, 2017)
Abstract. Caterpillar grayak (Spodoptera litura) is one of the pests in various types of vegetable plants are polyphagous and have a wide range of hosts. One common way of controlling farmers to overcome Spodoptera litura attack is to use insecticide. The use of insecticides that are not rational will accelerate the occurrence of pest resistance against insecticides. An alternative is needed to develop biological products which are generally narrow-spectrum chemicals to target organisms. Flowers at four (Mirabilis jalapa) contain bioactive compounds that are toxic. M. Jalapa contains some secondary metabolite compounds such as saponins, flavonoids, tannins, and polyphenols. Based on the description above it is necessary to conduct a research to determine the percentage mortality of caterpillar grayak on giving the leaf extract at four o'clock flowers. The method used is leaf dipping methods and analysis with POLO-PC software. The results showed that 1.6% concentration of extract of M. jalapa can kill the number of larvae as much as 30 tails with a percentage of 75% within 48 hours. The LC50 value of mortality of M. jalapa extract on Spodoptera litura larvae was 0,507% (0,378-0,661 with p <0,05) with slope1,516 Â± 0,318.Keywords: Bioinsecticides, Mirabilis jalapa, Spodoptera litura, MortalityÂ